2019
DOI: 10.9770/jssi.2019.9.1(4)
|View full text |Cite
|
Sign up to set email alerts
|

Ensuring Complex Security of the Financial Flows Movement in the National Economy System

Abstract: The individual principles of the cyclical course of economic processes in modern economic conditions were considered. The existing theories of economic (business) cycles were analyzed. The financial economy was defined as a component of the security of financial flows. The factors of strengthening (weakening) of the interaction of financial flows in the economy and their safe movement support were characterized. The effect of multiplication of financial flows for individual stages of the economic cycle was dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The illegal incomes that flow through a country's financial system significantly affect its economic security and can cause not only the loss of financial stability of banks, insurers, etc., but also lead to an increase in crime and terrorist attacks in the state. The study suggests that the tools for the state's economic security should be based on a detailed study of the processes that provide it or may violate it (Kamaliah et al, 2018;Katan et al, 2019). Thus, the anti-money laundering system should be able to quickly adapt and change since the results of the scientific and methodological approach to assessing the risks of using Ukrainian financial institutions for money laundering indicate its low efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…The illegal incomes that flow through a country's financial system significantly affect its economic security and can cause not only the loss of financial stability of banks, insurers, etc., but also lead to an increase in crime and terrorist attacks in the state. The study suggests that the tools for the state's economic security should be based on a detailed study of the processes that provide it or may violate it (Kamaliah et al, 2018;Katan et al, 2019). Thus, the anti-money laundering system should be able to quickly adapt and change since the results of the scientific and methodological approach to assessing the risks of using Ukrainian financial institutions for money laundering indicate its low efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…Many works, in particular, (Bausch, 2019), (Bilan et al, 2019a(Bilan et al, , 2018, (Brychko & Olejarz, 2019), (Munk et al, 2017), (Rudiawarni et al, 2020), (Vasilyeva et al, 2016(Vasilyeva et al, , 2019, (Shvindina, 2019) deal with the study of financial and business cycles based on time series analysis (seasonal, trend, cyclical component separation). Also there are a lot investigations about behavioral aspects in financial inclusion ( (Brychko, 2013), (Churilova et al, 2019), (Cortés-Sánchez & Rivera, 2019), (Djajanto et al, 2019), (Djalilov et al, 2015), (Hadbaa & Boutti, 2019), (Kaasa, 2019), (Katan et al, 2019), (Kolomiiets & Petrushenko, 2017), (Matošková, 2019), (Němcová & Staňková, 2019)) and protection of consumers ( (Piatek, 2018), (Poliakh, 2018), (Rehman, 2020), (Shapovalova et al, 2019), (Mihalčová et al, 2018)). Many scientific papers have found that the social safety of the population is also determined by the macroeconomic situation of the country (Aqil et al, 2019), (Bilan et al, 2019b, (Logan & Esmano, 2017), (Próchniak & Szyszko, 2019), (Packard et al, 2019); alternative factors related to the development of other sectors of the economy (industry, banking, investment, education) (Bilan et al, 2019c); (Buriak, 2015), (Ch & Semenog, 2017), (Klimontowicz, 2019), (Leonov et al, 2014(Leonov et al, , 2019, …”
Section: Literature Reviewmentioning
confidence: 99%
“…Institutions of market stabilizationinstitutions of monetary circulation and tax regulation, prudential regulation and supervision, institutions of risk coordination and sharing (for example, a banking and credit system, tax authorities, stock market, pension funds, private and state venture companies, and agencies). Countries need monetary, fiscal and other measures to combat economic cycles (Katan et al 2019). Ensuring complex security of the financial flows movement in the national economy system, Journal of Security and Sustainability Issues 9(1): 39-50..…”
Section: Determinant Which Characterizes Institutionsmentioning
confidence: 99%